Diagnosis and feedback system for bicycle pedaling technique and its application - Luo, J.; Zheng, B. (Proceedings of the International Conference on Future Computer Science and Education, 2011, 2011)
This diagnosis and feedback system for bicycle pedaling technique has been designed with VF 6.0. This system includes 5 modules which are 2-D image analysis, dynamics parameters collection, data analysis, parameters assessment, and athletes data. 2-D image analysis has been developed to suit for the characteristics of the pedaling technique. Through dynamics parameters collection, 2-D or 3-D forces of the pedals, handlebars, and saddle can be obtained. Kinematics and dynamics parameter can be obtained and be stored into the database of the diagnosis system concurrently. User can obtain an athlete data or more to analyze and compare them, and can compare between common athletes and elite athletes or among elite athletes. This system is easy to use, especial for the coaches. This system integrates data collection, analysis, and store.